Outbreak of scrub typhus in western part of India: containment and lessons learnt - Patel, Barun Bhai; Gurmeet, Pranaya; Dutt, Vipul; Singh, Harpreet; Sharma, Amit; Gupta, Vivek; Pandya, Kapil H.; Madne, Ganesh; Bhattacharya, Indrakhi; Gupta, Paridhi (International Journal Of Community Medicine And Public Health, 2023)
Background: Scrub typhus is one of the most covert diseases of present era. Diagnosis is often missed, and tools for confirming diagnosis are often not available in resource-poor setups. The aim of the study was to investigate an outbreak investigation and suggests methods of containment. Methods: An epidemiological investigation of Scrub typhus outbreak though active and passive surveillance. Time, Place and person distribution, mean, median stand deviation were used during analysis. Results: Cases presented with high grade fever (100%), bodyache (91%) and headache (81%). Nearly, 22% cases presented with Eschar, 16% of blood samples were positive for OX-19 antigens, 9% blood samples were sent for enzyme linked immunosorbent assay (ELISA) and were positive for IgM antibodies. Conclusions: An outbreak of Scrub Typhus infection was successfully contained without any mortality by effectively using Chemoprophylaxis, judicial use of chemicals and personal protective measures.